The German experiment: health care without female or Jewish doctors - Alexa R. Shipman, BMBCh, MRCP (Wolters Kluwer, 2017)
Jewish and female doctors were not allowed to practice medicine in Germany during Hitler's rule from 1933 to 1945. Data about the consequences of this on the health service are difficult to come by, but what information can be gathered demonstrates a detrimental effect on the nation's health. These data, however, must be interpreted with consideration to the morbidity and mortality from violence, death camps, slave labor, and the privations of war. The article summarizes the history of German health care during this period and also compares Germany to other nations at that time.